1967
DOI: 10.1152/ajplegacy.1967.213.5.1138
|View full text |Cite
|
Sign up to set email alerts
|

Biliary excretion and enterohepatic circulation of estrone and estriol in rodents

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

1969
1969
2000
2000

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…An enterohepatic circulation of lignans occurs; they are absorbed from the intestine, transferred to the liver and conjugated, excreted in bile and reabsorbed mainly as conjugates. Their physiological behaviour resembles cholesterol [1720],bile acids [21] bile pigments [22],oestrogens [23,24],vitamin Blz [25] andfolicacid [26,27],compounds which also have an enterohepatic circulation.…”
Section: Discussionmentioning
confidence: 99%
“…An enterohepatic circulation of lignans occurs; they are absorbed from the intestine, transferred to the liver and conjugated, excreted in bile and reabsorbed mainly as conjugates. Their physiological behaviour resembles cholesterol [1720],bile acids [21] bile pigments [22],oestrogens [23,24],vitamin Blz [25] andfolicacid [26,27],compounds which also have an enterohepatic circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Sandberg et al (1967) after administration of oestrone to intact rabbits re¬ covered 69 % of the dose in the urine and 16% in the faeces; in animals with a bile fistula 17% was recovered in the bile and the amount in the urine (36 %) was reduced, suggesting a substantial enterohepatic circulation. After administration of large doses of oestradiol to rabbits, Collins et al (1967) re¬ covered about 80 % in the urine over a period of 20 days.…”
Section: E Metabolism Of Oestrogens In Rabbitsmentioning
confidence: 98%
“…Several in vivo studies in the same species suggested that little other than glucuronides were to be found in urine ( 5 , 6 ) or bile (5). Guinea pig liver perfusion experiments (7) failed to detect additional types of conjugates.…”
Section: Introductionmentioning
confidence: 99%